Systematic Literature Review: Analysis Of User Interface (Ui) Design Methods In Mobile Application Development - Diharphyta Ningrum Hadijoyo; Najla Alsyafanissa Putri Hidayat; Rezqita Dwimarsya Fathania (PT Jurnal Cendekia Indonesia, 2025)
User interface (UI) design are vital elements in the mobile application development process to ensure user comfort, ease of use, and satisfaction. Various approaches to UI design have been tested in various mobile application research and development projects, but there has been no comprehensive analysis of the effectiveness and trends in the application of these methods. This study aims to evaluate various UI design methods applied in mobile application development through a Systematic Literature Review (SLR) approach. The SLR process was carried out by following the steps of identifying, selecting, and analyzing scientific publications published within a certain time frame. The results of this study reveal that the most commonly used methods are User Centered Design (UCD) and Design Thinking. Each method has advantages and limitations related to the effectiveness of the design process, the level of user participation, and its impact on the quality of the user experience. In addition, there has been an observed trend of increasing use of collaborative and iterative methods in recent years. These findings can be used as a guide for researchers and mobile application developers in choosing the UI approach that best suits the needs of their project.